1997
DOI: 10.1021/bi962996p
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in Cholera Toxin B Subunit−Ganglioside GM1 Complexes Are Elicited by Environmental pH and Evoke Changes in Membrane Structure

Abstract: Fluorescence resonance energy transfer (FRET) was used to monitor pH-dependent structural changes in the cholera toxin B subunit (CTB) and the membranes with which CTB associates. The distance separating the single tryptophan (Trp88) of each CTB monomer and a pyrene probe linked to the membrane-imbedded tail of ganglioside GM1 is not influenced by pH in a range from 3.5 to 7.5, consistent with the position of Trp88 in the GM1 binding site of CTB. In contrast, the distance between the pyrene probe on GM1 and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Indeed, the ER-targeted toxins Shiga toxin and cholera toxin are closely related AB5 toxins that recognize glycolipids. Once in the endosome lumen, low pH induces in these toxins only subtle conformational changes that are unrelated to membrane penetration (29,31). These toxins eventually reach the ER, where they can be visualized (27,52).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the ER-targeted toxins Shiga toxin and cholera toxin are closely related AB5 toxins that recognize glycolipids. Once in the endosome lumen, low pH induces in these toxins only subtle conformational changes that are unrelated to membrane penetration (29,31). These toxins eventually reach the ER, where they can be visualized (27,52).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these results indicate that the slow mobility of the bound CTB cannot be ascribed simply to an increased surface level of CTB-GM1 as a result of stimulated outward trafficking. Slow lateral diffusion of CTB-GM1 has been observed in other cell types (Bacia et al, 2002;Kenworthy et al, 2004), and its physical basis remains to be determined, although it has been suggested to be pH dependent (McCann et al, 1997;Pelkmans et al, 2004). In any case, this slow lateral mobility causes freshly delivered CTB-GM1 to accumulate at a targeting site that corresponds to the clustered IgE receptors and initial stimulus.…”
Section: Localized Targeting Of Recycling Endosomesmentioning
confidence: 99%
“…Apparently, the loss of the hydrogen bonds between the terminal galactose and either Glu-51 or Lys-91 does not dramatically affect GM 1 binding in vitro. The interactions between Glu-51 and Lys-91, together with His-57 (all conserved between CT and LT-I), have been proposed in LT-I to be involved in a pH-dependent conformational change of the pentamer (33), a change that also occurs with CTB (22,33). Efforts in those studies to make site-directed mutations for Glu-51 and Lys-91 in the B subunit of LT-I were unsuccessful, leading to the suggestion that these mutations were toxic to the E. coli host.…”
Section: Vol 70 2002mentioning
confidence: 99%